Measuring earnings inequality and median earnings in the tourism industry - Lee, Choong-Ki; Kang, Seyoung (Tourism management (1982), 1998)
The purpose of this paper is two-fold: to measure the degree of earnings inequality in tourism employees in South Korea, using the Gini coefficient and the Lorenz curve; and to examine the level of earnings based on median earnings. The results show that tourism generates a moderately equal distribution of earnings. In general, tourism performs earnings distribution better than secondary and tertiary industries, but it performs poorly as compared with primary industry. The results also indicate that tourism is more likely to improve living standards for the lower income class than secondary and tertiary industries. The analysis of median earnings, however, indicates that tourism is a low wage industry. The labor-intensive nature of the tourism industry absorbing many unskilled and semi-skilled workers might be attributed to its low wage structure. It is interesting to note that tourism was found to be advantageous to female workers in terms of earnings inequality and the level of earnings.